An overview of water electrolysis technologies for the production of hydrogen - Saravanan, Prabhu; Rahman, Md Mustafizur; Chin, Sim Yee; Vo, Dai-Viet N. (Elsevier, 2020)
Hydrogen is a clean form of energy, which should replace the conventional energy system depending on fossil fuel combustion. Hydrogen is the main constituent of fossil fuels along with carbon, hence fossil fuel and the biomass are considered as the main feed for hydrogen generation. To eliminate the carbon footprint, water is preferred to derive hydrogen to build a sustainable future. Water electrolysis technologies to produce hydrogen are sustainable and environmentally harmless compared to the thermochemical hydrogen production processes. This chapter presents the overview of the most important categories of the technologies for water electrolysis such as conventional electrolysis of water, microbial, carbon, or hydrocarbon and photoelectrochemical (PEC)-aided water electrolysis. The green and clean hydrogen production by PEC/perovskite solar cell (PSC) method have gained significant advantages over others. However, the challenging factors such as low-cost fabrication methods and development of potential semiconductor catalysts should be addressed for large-scale hydrogen production.